Training on results-based monitoring and evaluation a 'good experience' - Yadeto, T. (International Livestock Research Institute, 2012)
Tirfu Yadeto participated in the recent IPMS-supported Training of Trainers (ToT) workshop on result-based monitoring & evaluation (November 28-December 3, 2011, Debre Zeit Ethiopia).